(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The etymology, lexical and semantic functions, word-formation opportunities of a word «toady» in texts of art, social and political essays, official – business styles are investigated in this article.